Repeating Earthquakes at the Edge of the Afterslip of the 2016 Ecuadorian MW 7.8 Pedernales Earthquake. Issue 5 (4th May 2021) - Chalumeau, Caroline; Agurto‐Detzel, Hans; De Barros, Louis; Charvis, Philippe; Galve, Audrey; Rietbrock, Andreas; Alvarado, Alexandra; Hernandez, Stephen; Beck, Susan; Font, Yvonne; Hoskins, Mariah C.; León‐Ríos, Sergio; et al.
Abstract: Repeating earthquakes repeatedly rupture the same seismic asperity and are strongly linked to aseismic slip. Here, we study the repeating aftershocks of the April 16, 2016 MW 7.8 Pedernales earthquake in Ecuador, which generated a large amount of afterslip. Using temporary and permanent stations, we correlate waveforms from a one‐year catalog of aftershocks. We sort events with a minimum correlation coefficient of 0.95 into preliminary families, which are then expanded using template‐matching to include events from April 2015 to June 2017. In total, 376 repeaters are classified into 62 families of 4–15 events. They are relocated, first using manual picks, and then using a double difference method. We find repeating earthquakes during the whole period, occurring primarily within large aftershock clusters on the edges of the areas of largest afterslip release. Their recurrence times, shortened by the mainshock, subsequently increase following an Omori‐type law, providing a timeframe for the afterslip's deceleration. Although they are linked temporally to the afterslip, repeater‐derived estimates of slip differ significantly from GPS‐based models. Combined with the fact that repeaters appear more spatially correlated with the afterslip gradient than with the afterslip maxima, we suggest that stress accumulation at the edge of the afterslip may guide repeater behavior. Plain Language Summary: Ecuador, where the oceanic Nazca plate sinks under South America, is home to many earthquakes, like the 16th of April 2016 event that occurred near the city of Pedernales. This event generated smaller earthquakes (aftershocks), and slow, nondestructive slip (afterslip). Some aftershocks were repeating earthquakes, which are earthquakes that happen in the same spot multiple times. This type of event is usually caused by slow slip happening around it. Within a large slowly slipping area, stress will accumulate at locked, unmoving spots called asperities, that then break intermittently, causing repeating earthquakes. This means that by studying repeating earthquakes, we can measure the slow slip happening around them. In our study, we look for repeaters during the year before and after the Pedernales earthquake. We find repeaters primarily in large earthquake groups at the edge of the areas where afterslip happened. However, the measures of slow slip we calculated using repeaters and the estimates we calculated with GPS do not match. This, and the location of the repeaters around the slow slip areas rather than inside them, means that the repeaters might not be directly related to the slip amount, but to the stress accumulation at the edge of the slow‐slip area. Key Points: Repeating earthquakes are found in Ecuador in the aftermath of the MW 7.8 2016 Pedernales earthquake Repeaters occur primarily in large clusters at the edges of the afterslip patches, where afterslip gradient is high Repeaters may respond to stress accumulation at the edge of the afterslip